PKM REVITALIZATION OF MONKEY CAVE IN KELAPA LIMA DISTRICT KUPANG CITY, NTT PROVINCE - Rifat Y.Y. Maromon; Suliha N.I. Neonufa; Linda W. Fanggidae; Dwi Y.Y. Prasetyo; Lodwik O. Mahoklory (Sekolah Vokasi Universitas Diponegoro, 2025)
The Five Coconut Monkey Cave in Kupang City has been affected by the development of the Kupang City area. Around the 2000s, there were still several groups of monkeys roaming the location but gradually became extinct due to collisions, hunting, and disappearing from the area. As the name of the Monkey Cave Area but in it is no longer a monkey habitat, of course it is a question for tourists who visit and is the hope of the NTT Provincial Tourism and Creative Economy Office. Therefore, to restore or re-function as a monkey residence or there are other alternatives that can be developed can be a reference of university service to the Government and the community in general.